(3eLeY GdahGFO dLe GdYhGFOs - (3aGWeI HfJ eMeO Hf CMeO SeQbfOis; (3GdQGRj , Rjf GdOjf eMeO Hf TeS GdOjf CHj HcQ Hf YHO GdbGOQ GdMfaj GdQGRj,J (B666 (3g` s ((3eMeO Hf EHQGgje s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYdfG ef Cgd GdESdGe hHYO adeG QCjJ Cf NjQ GdYdhe HYO eYQaI CUd GdOjf Yde Gdabg CQOJ Cf CTQM dg TQMkG eTJedkG Ydi JbQjQ eSGFc s
(3BNQgG (B:s
(3aYdjc CjgG GdCN HGdJbhi hGdESJYOGO ddbGA Gddg YR hLd hfYje GdBNQI hGddg CYde HGdUhGH Je GdcJGH HYhf Gddg Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs